2020
DOI: 10.32394/pe.74.21
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus diseases and pregnancy: COVID-19,SARS, and MERS

Abstract: Around the end of December 2019, a new beta-coronavirus from Wuhan City, Hubei Province, China began to spread rapidly. The new virus, called SARS-CoV-2, which could be transmitted through respiratory droplets, had a range of mild to severe symptoms, from simple cold in some cases to death in others. The disease caused by SARS-CoV-2 was named COVID-19 by WHO and has so far killed more people than SARS and MERS. Following the widespread global outbreak of COVID-19, with more than 132758 confirmed cases and 4955… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…However, vertical transmission seems to occur in a minority of cases of maternal COVID-19 infection in the third trimester ( 31 , 32 ). Consistent with several studies ( 33 36 ), we found no evidence of vertical transmission. Thus, we believe that there is still no definite evidence of vertical transmission of SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 92%
“…However, vertical transmission seems to occur in a minority of cases of maternal COVID-19 infection in the third trimester ( 31 , 32 ). Consistent with several studies ( 33 36 ), we found no evidence of vertical transmission. Thus, we believe that there is still no definite evidence of vertical transmission of SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 92%
“…12, [21][22]24,30,[33][34]40,42,[47][48]50,[52][53][58][59]62,65,74,76 At least one maternal death. 9,16,17,23,[25][26][27][28]32,[35][36][37][38][39]41,[44][45][46]49,51,54,55,60,63,64,[66][67][68][71][72][73]75,[77][78][79]…”
Section: Outcome Of Maternal Death Due To Covid-19mentioning
confidence: 99%
“…It has been reported that the route of transmission is the placenta and amniotic membranes [10]. These membranes are reported to have a large surface area that is very close to the maternal decidual and can also serve as a conduit for transmission from the maternal side to the fetus [10] [11].…”
Section: In Utero Transmission Of Coronavirusmentioning
confidence: 99%